Pharmaceutical analysis and quality of complementary medicines : sceletium and associated products - Patnala, Satya Siva Rama Ranganath Srinivas (Rhodes University, Faculty of Pharmacy, Pharmacy, 2007)
There has been an upsurge in the use of Complementary and Alternate Medicines (CAMs) in both developed and developing countries. Although herbal medicines have been in use for many centuries, their quality, safety and efficacy are still of major concern. Many countries are in the process of integrating CAMs into conventional health care systems based on the knowledge and use of traditional medicines. The quality control (QC) of herbal products usually presents a formidable analytical challenge in view of the complexity of the constituents in plant material and the commercial non-availability of appropriate qualified reference standards. Sceletium, a genus belonging to the family Aizoaceae, has been reported to contain psychoactive alkaloids, specifically mesembrine, mesembrenone, mesembrenol and some other related alkaloids. Sceletium is marketed as dried plant powder and as phyto-pharmaceutical dosage forms. Sceletium products and plant material marketed through health shops and on the internet are associated with unjustified claims of specific therapeutic efficacy and may be of dubious quality. Validated analytical methods to estimate Sceletium alkaloids have not previously been reported in the scientific literature and the available methods have focused only on qualitative estimation. Furthermore, since appropriate markers were not commercially available for use as reference standards, a primary objective of this study was to isolate relevant compounds, qualify them as reference standards which could be applied to develop appropriate validated qualitative and quantitative analytical methods for fingerprinting and assay of Sceletium plant material and dosage forms. The alkaloidal markers mesembrine, mesembrenone and âˆ†â · mesembrenone were isolated by solvent extraction and chromatography from dried plant material. Mesembranol and epimesembranol were synthesised by hydrogenation of the isolated mesembrine using the catalyst platinum (IV) oxide and then further purified by semi-preparative column chromatography. All compounds were subjected to analysis by Â¹H, Â¹Â³C, 2-D nuclear magnetic resonance and liquid chromatography-tandem mass spectroscopy. Mesembrine was converted to hydrochloride crystals and mesembranol was isolated as crystals from the hydrogenation reaction mass. These compounds were analysed and characterised by X-ray crystallography. A relatively simple HPLC method for the separation and quantitative analysis of five relevant alkaloidal components in Sceletium was developed and validated. The method was applied to determine the alkaloids in plant material and dosage forms containing Sceletium. An LCMS method developed during the study provided accurate identification of the five relevant Sceletium alkaloids. The method was applied for the quantitative analysis and QC of Sceletium plant material and its dosage forms. This LCMS method was found to efficiently ionize the relevant alkaloidal markers in order to facilitate their detection, identification and quantification in Sceletium plant material as well as for the assay and QC of dosage forms containing Sceletium. The chemotaxonomy of some Sceletium species and commercially available Sceletium dosage forms were successfully studied by the LCMS method. The HPLC and LCMS methods were also used to monitor the bio-conversion of some of the alkaloids while processing the plant material as per traditional method of fermentation. Additionally a high resolution CZE method was developed for the separation of several Sceletium alkaloids in relatively short analysis times. This analytical method was used successfully to fingerprint the alkaloids and quantify mesembrine in Sceletium and its products. Sceletium species grown under varying conditions at different locations, when analyzed, showed major differences in their composition of alkaloids and an enormous difference was found to exist between the various species with respect to the presence and content of alkaloids. Sceletium and its products marketed through health shops and the internet may thus have problems with respect to the quality and related therapeutic efficacy. The QC of Sceletium presents a formidable challenge as Sceletium plants and products contain a complex mixture of compounds. The work presented herein contributes to a growing body of scientific knowledge to improve the QC standards of herbal medicines and also to provide vital information regarding the selection of plant species and information on the specific alkaloidal constituents to the cultivators of Sceletium and the manufacturers of its products.
Keywords: Alternative medicine; Herbs -- Therapeutic use